Predictors of COVID-19 Preventive Behavior Adoption Intention in Malaysia - Mat Dawi, Norazryana; Namazi, Hamidreza; Maresova, Petra (Frontiers in Psychology, 2021)
Preventive behavior adoption is the key to reduce the possibility of getting COVID-19 infection. This paper aims to examine the determinants of intention to adopt preventive behavior by incorporating perception of e-government information and services and perception of social media into the theory of reasoned action. A cross-sectional online survey was carried out among Malaysian residents. Four hundred four valid responses were obtained and used for data analysis. A partial least-square-based path analysis revealed direct effects of attitude and subjective norm in predicting intention to adopt preventive behavior. In addition, perception of e-government information and services and perception of social media were found to be significant predictors of attitude toward preventive behavior. The findings highlight the importance of digital platforms in improving people’s attitudes toward preventive behavior and in turn contain the spread of the infectious disease.